2022
DOI: 10.1136/bmjgast-2022-000987
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of incoming and outgoing second opinions from a UK liver transplant centre

Abstract: ObjectiveSecond transplant centre opinions (STCOs) for patients declined for liver transplantation are infrequent. We aimed to identify STCOs outcomes from a tertiary transplant centre.DesignReferrals between 2012 and 2020 to Birmingham Unit were reviewed. Incoming: all referrals from out-of-region centres were collated. Outgoing: patients not listed in Birmingham were reviewed to identify referrals for STCOs to the other UK centres (A–F).Results2535 patients were assessed for liver transplantation during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the United Kingdom, 1 study demonstrated that virtual, multidisciplinary discussions between transplant programs is feasible, may negate the need for patient travel, and can be performed in an expedited fashion. [11] However, virtual discussions based on the first center's experience may unduly influence or bias the second center. For more nuanced decisions, such as psychosocial evaluations, 1 potential solution may be to conduct virtual specialtyrelevant evaluations by the second center prior to transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, 1 study demonstrated that virtual, multidisciplinary discussions between transplant programs is feasible, may negate the need for patient travel, and can be performed in an expedited fashion. [11] However, virtual discussions based on the first center's experience may unduly influence or bias the second center. For more nuanced decisions, such as psychosocial evaluations, 1 potential solution may be to conduct virtual specialtyrelevant evaluations by the second center prior to transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to share medical testing results and committee decisions may allow for pre-transfer screening protocols and save on health care and administrative costs associated with transfer and re-evaluation. In the United Kingdom, 1 study demonstrated that virtual, multidisciplinary discussions between transplant programs is feasible, may negate the need for patient travel, and can be performed in an expedited fashion 11 . However, virtual discussions based on the first center’s experience may unduly influence or bias the second center.…”
Section: Discussionmentioning
confidence: 99%